Burrower Bugs Described After the Cydnidae of the Western Hemisfere catalogue 1960 (Hemiptera, Hetroptera, Cydnidae) - Magnanelli, Marco Andres (2011)
An update to the catalogue of the Cydnidae (Hemiptera) of the Western Hemisphere (Froeschner 1960) is given. A total of 6 genera and 21 species are listed together with their synonyms. References are given for the original descriptions and the subsequent taxonomic position, the location of types, and the geographic distribution. A comprehensive bibliography is provided.